2022
DOI: 10.1136/bmjopen-2021-054420
|View full text |Cite
|
Sign up to set email alerts
|

Association between metformin use and the risk of age-related macular degeneration in patients with type 2 diabetes: a retrospective study

Abstract: ObjectivesTo investigate the effect of metformin on the decreased risk of developing age-related macular degeneration (AMD) in patients with type 2 diabetes mellitus (T2DM) for ≥10 years.DesignA retrospective study.ParticipantsPatients aged ≥50 with a diagnosis of T2DM no less than 10 years were included.MethodsVariables predisposing to AMD were reviewed; the potential confounders related to T2DM or AMD were selected from literature records; AMD and diabetic retinopathy (DR) were diagnosed by funduscopy, optic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(36 citation statements)
references
References 51 publications
1
35
0
Order By: Relevance
“…The included studies consisted of one cross-sectional, 19 three case‒control, 12 , 13 , 18 and five cohort studies. 14 17 , 20 Eight studies were retrospective in design, 12 19 and one was conducted prospectively. 20 Four studies were performed in the United States, 12 , 13 , 15 , 19 three in Asia, 14 , 17 , 18 and the other two in Europe.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The included studies consisted of one cross-sectional, 19 three case‒control, 12 , 13 , 18 and five cohort studies. 14 17 , 20 Eight studies were retrospective in design, 12 19 and one was conducted prospectively. 20 Four studies were performed in the United States, 12 , 13 , 15 , 19 three in Asia, 14 , 17 , 18 and the other two in Europe.…”
Section: Resultsmentioning
confidence: 99%
“… 14 17 , 20 Eight studies were retrospective in design, 12 19 and one was conducted prospectively. 20 Four studies were performed in the United States, 12 , 13 , 15 , 19 three in Asia, 14 , 17 , 18 and the other two in Europe. 16 , 20 Seven studies obtained a diagnosis of DM with International Classification of Diseases (ICD) codes, 12 15 , 17 19 one with database read codes, 16 and one with medical records.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, prospective trials should not only concentrate on late-stage dry AMD but consider all AMD stages. Jiang et al [41] found for example, that especially the early stage of AMD was associated with a beneficial effect of metformin. Finally, prospective trials should consider patients with and without a diagnosis of diabetes to rule out possible confounding effects of the diabetic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Eight retrospective studies have analyzed the association of metformin use with AMD, of which one was a crosssectional study [39], four were cohort studies [40][41][42][43], two were case-control studies [44,45], and one was a nested case-control study [46]. Five studies exclusively determined the association between metformin use and the risk of developing AMD in diabetic patients [39][40][41][42][43], whereas three studies included broader patient groups according to their cohort definition [44][45][46]. One study examined the association of metformin use with dry AMD only [43], while the remaining studies considered all forms of AMD or did not further specify.…”
Section: Effects Of Metformin Use On Amd In Retrospective Clinical Tr...mentioning
confidence: 99%
See 1 more Smart Citation